Women's Entrepreneurship in the Creative Industries: Impact on the Economy of the Republic of Serbia - Dušan STOJAKOVIĆ; Milena ILIĆ P.; Nevenka POPOVIĆ ŠEVIĆ; Bojan S. RISTIĆ; Milica SLIJEPČEVIĆ (Communications of International Proceedings, 2021)
The creative industries in the Republic of Serbia have a share in the GDP between 3.4% and 7.1%, depending on the concept of observation, with faster growth than the rest of the economy, so they represent an important sector in both a number of economies of developed countries and the Republic of Serbia. According to official data, more than 115,000 employees are employed in the creative industries sector of Serbia within more than 30,000 registered enterprises. Using the available data, there is perception that the employees in the creative industries are between the ages of 25 and 44, half of them with a university degree. Also, the share of women in the creative industries of Serbia is evident.  These industries provide numerous opportunities for the development of women's entrepreneurship. Their better understanding is needed, which is the purpose of this paper. The original contribution of the paper is reflected in its systematicity and analytical and practical implications. Comparing the results in the field of innovation implementation in the Republic of Serbia has led to concrete results, which could be a positive signal for the participation of even more female entrepreneurs in the field of creative business.
Keywords: Entrepreneurship; women's entrepreneurship; creative industries; cultural entrepreneurs; economic development; innovation